ABUDANCE AND DISTRIBUSION PATTERN OF GASTROPOD AT INTERTIDAL ZONE KALANGAN COAST TAPANULI TENGAH SUMATERA UTARA PROVINCE - Judika Nursiani Sipahutar; Efriyeldi Efriyeldi; Aras Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTCoastal ecosystems are the confluence of land and sea that are still influenced by sea characteristics such as tides, sea breezes and salt intrusion and sedimentation processes.The intertidal zone is part of a coastal ecosystem in which many marine biota live such as the gastropods of the mollusk phylum. The purpose of this study was to determine the type and abundance as well as the distribution pattern of gastropods in the intertidal zone of Kalangan Beach in Central Tapanuli, North Sumatra. This research was conducted in April 2019. From the results of the study it was found that in the intertidal zone of the Kalangan Beach 10 gastropods were found, namely Clypeomorus sp, Littorina sp, Polinices, Clypeomorus bifascita, Nassa francolinus, Morula granulata, Phasianella solida, Clypeomorus batillariaeformis, Cerithiium sp,and Faunus ater. At station I with an abundance of 5 ind / m2 which is relatively low. At station II with an abundance value of 2 ind / m2 classified as very low, and at station III with an abundance value of 43 ind / m2 classified as abundant. The distribution pattern of gastropods in the intertidal zone of Kalangan Beach at each station is clustered. Keywords:gastropods, abundance, distribution pattern